2009
DOI: 10.1007/s11606-009-1011-z
|View full text |Cite
|
Sign up to set email alerts
|

Did Duty Hour Reform Lead to Better Outcomes Among the Highest Risk Patients?

Abstract: ACGME duty hour reform was not associated with any consistent improvements or worsening in mortality or failure-to-rescue rates for high risk medical or surgical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 35 publications
4
67
0
Order By: Relevance
“…Our fi ndings are consistent with studies showing that in-hospital outcomes for patients in the ICU improved over this time period independent of work-hour reforms. [43][44][45][46][47][48][49][50][51][52][53][54] Taken together, these results support the view that an ICU's readmission rate refl ects operational policies or practice variation not in the causal pathway to mortality. Th is conclusion is supported by complementary data indicating that the readmission rate of an ICU is uncorrelated with performance on other measures of ICU quality.…”
Section: Discussionsupporting
confidence: 64%
“…Our fi ndings are consistent with studies showing that in-hospital outcomes for patients in the ICU improved over this time period independent of work-hour reforms. [43][44][45][46][47][48][49][50][51][52][53][54] Taken together, these results support the view that an ICU's readmission rate refl ects operational policies or practice variation not in the causal pathway to mortality. Th is conclusion is supported by complementary data indicating that the readmission rate of an ICU is uncorrelated with performance on other measures of ICU quality.…”
Section: Discussionsupporting
confidence: 64%
“…Rosen et al demonstrated that in Medicare and VA patients, most patient safety indicators (PSIs), which are adverse events that are identifiable in administrative data, 77 were equally common in both time periods, although certain PSIs occurred more often in the post-duty hour time period in the VA patients (OR 1.63). 78 Silber et al found no increased risk of prolonged hospitalization in Medicare or VA patients. 79 …”
Section: Complicationsmentioning
confidence: 97%
“…1 The new guidelines reiterated the 2003 recommendations (maximum of 80 h of work per week and direct patient care shifts no longer than 24 + 4 h) and restricted post-graduate year 1 (PGY-1) trainees to a maximum shift length of 16 h, with a minimum of 8 h off between shifts. 2,3 Studies of 2011 models, similar to outcomes following 2003 changes, [4][5][6][7][8] have yet to show any improvements in quality of care, 9-12 trainee education, 11 or resident well-being. 13 Also, program director and resident surveys have conveyed strong concerns about sacrificing continuity of care and educational activities for DHR compliance.…”
Section: Introductionmentioning
confidence: 99%